2015
DOI: 10.1519/jsc.0000000000000927
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Lower Limb Muscle Activity and Platform Acceleration During Whole-Body Vibration Exercise

Abstract: The purpose of this study was to identify the influence of different magnitudes and directions of the vibration platform acceleration on surface electromyography (sEMG) during whole-body vibration (WBV) exercises. Therefore, a WBV platform was used that delivers vertical vibrations by a side-alternating mode, horizontal vibrations by a circular mode, and vibrations in all 3 planes by a dual mode. Surface electromyography signals of selected lower limb muscles were measured in 30 individuals while they performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
34
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 41 publications
3
34
1
Order By: Relevance
“…In addition, in the present study the displacement of the vibrating plate was not constant but 24 tended to increase, increasing the vibration frequency, and therefore we underline, as previously reported (Lienhard et al 2015), that the acceleration load rather than a vibration 1 frequency should be considered as the most important parameter for optimization of the 2 beneficial effects of WBV.…”
supporting
confidence: 64%
See 4 more Smart Citations
“…In addition, in the present study the displacement of the vibrating plate was not constant but 24 tended to increase, increasing the vibration frequency, and therefore we underline, as previously reported (Lienhard et al 2015), that the acceleration load rather than a vibration 1 frequency should be considered as the most important parameter for optimization of the 2 beneficial effects of WBV.…”
supporting
confidence: 64%
“…Interestingly, Lienhard et al (2015) have found a linear relationship between the vertical 10 platform acceleration and the lower body sEMG RMS . However, by this study the relationship 11 has not been specified in each leg muscle but, for analysis, it has been considered the average 12 value of different leg muscles.…”
mentioning
confidence: 97%
See 3 more Smart Citations